A Comparative Study of Three Indonesian Islands on The Performance in Mathematics - Devi Anggriyani; Martin Iryayo; Harun Rasyid (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
The level of performance among Indonesian students in Mathematics is still critical. This study aims at comparing provinces within each of three islands, and then all three Islands in general, the comparison focused on the performance in mathematics during 2014/2015 national examination. Islands involved in the current research are Java, Sumatera, and Kalimantan. For each province from every island, the researchers selected urban districts by using the formula of Krecie & Morgan (1970), with .05 degree of accuracy, and then systematic sampling to select schools. On Java Island, the researchers selected 669 out of 1065 schools, 508 out of 621 schools on Sumatera Island, and 203 out of 235 schools on Kalimantan Island. Gathering data involved documentation. The researchers analyzed the data by using NCSS 11 and JASP 0.8.3.1. The findings indicated a significant difference among provinces and even Islands on the performance in Mathematics, p<.01, and Sumatera is the most performing island in Mathematics.